An Analysis of Cohesive Devices in “The Drunk Text” Song by Henry Moodie - Diara April Hadiana; Zia Hisni Mubarak (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The employment of cohesive devices in the lyrics of Henry Moodie's song